Data on various allergen specific IgEs and prospective treatments on food-dependent exercise-induced anaphylaxis - Norihide Murayama; Kikuno Murayama (Data in Brief, 2018)
Food-dependent exercise-induced anaphylaxis (FDEIAn) is an anaphylactic reaction induced by physical exercise after ingestion of certain meals. FDEIAn is not very frequent, but recent case reports associated with various meals indicate an upward trend. Here, we report the data of various food specific IgEs and the clinical course of an experience with a patient who exhibited a unique FDEIAn reaction. Various food specific IgEs including staple food were positive with high levels. We could not find out the cause food of FDEIAn. Therefore we started preventive drug treatment. Specifically, only the skin symptoms (urticaria) were prevented by administering anti-histamine (hydroxyzine) daily, and respiratory symptoms (wheezing and distress) were prevented by daily administration of a leukotriene receptor antagonist (montelukast). Keywords: Multiple antigen positive, Food-dependent exercise-induced anaphylaxis (FDEIAn), Exercise-induced asthma (EIA), Leukotriene, Montelukast, Hydroxyzine